Comparison of metabolic and biomechanic responses to active vs. passive warm-up procedures before physical exercise - Brunner-Ziegler, S.; Strasser, B.; Haber, P. (The Journal of Strength and Conditioning Research, 2011)
Active warm-up before physical exercise is a widely accepted practice to enhance physical performance, whereas data on modalities to passively raise tissue temperature are rare. The study compared the effect of active vs. passive warm-up procedures before exercise on energy supply and muscle strength performance. Twenty young, male volunteers performed 3 spiroergometer-test series without prior warm-up and after either an active or passive warm-up procedure. Oxygen uptake (VO2), heart rate (HR), pH value, and lactate were determined at 80% of individual VO2max values and during recovery. Comparing no prior warm-up with passive warm-up, pH values were lower at the fourth test minute (p < 0.004), and lactate values were higher at the sixth and third minutes of recovery (p < 0.01 and p < 0.010, respectively), after no prior warm-up. Comparing active with passive warm-up, HR was lower, and Vo2 values were higher at the fourth and sixth test minutes (p < 0.033 and p < 0.011, respectively, and p < 0.015 and p < 0.022, respectively) after active warm-up. Differentiation between active and passive warm-up was more pronounced than between either warm-up or no warm-up. Conditions that may promote improved performance were more present after active vs. passive warm-up. Thus, athletes may reach the metabolic steady state faster after active warm-up.